2017
DOI: 10.1093/jxb/erx484
|View full text |Cite
|
Sign up to set email alerts
|

SmJAZ8 acts as a core repressor regulating JA-induced biosynthesis of salvianolic acids and tanshinones in Salvia miltiorrhiza hairy roots

Abstract: Jasmonates (JAs) are important plant hormones that regulate a variety of plant development and defense processes, including biosynthesis of secondary metabolites. The JASMONATE ZIM DOMAIN (JAZ) proteins act as negative regulators in the JA signaling pathways of plants. We first verified that methyl jasmonate (MeJA) enhanced the accumulation of both salvianolic acids and tanshinones in Salvia miltiorrhiza (Danshen) hairy roots by inducing the expression of their biosynthetic pathway genes. Nine JAZ genes were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 102 publications
7
61
0
Order By: Relevance
“…Further studies should be conducted to verify the network of interactions of LaJAZ proteins in vivo for figuring out potentials of LaJAZ formation in the jasmonate signaling. Much evidence suggests that JAZ proteins were involved in mediating the biosynthesis of specific secondary metabolites [56][57][58][59][60]. For example, JA enhances the accumulation of anthocyanin [61], and JAZ proteins interact with transcription factors or energy sensor SNF1-RELATED KINASE 1 (SnRK1) to affect anthocyanin accumulation [56,57].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Further studies should be conducted to verify the network of interactions of LaJAZ proteins in vivo for figuring out potentials of LaJAZ formation in the jasmonate signaling. Much evidence suggests that JAZ proteins were involved in mediating the biosynthesis of specific secondary metabolites [56][57][58][59][60]. For example, JA enhances the accumulation of anthocyanin [61], and JAZ proteins interact with transcription factors or energy sensor SNF1-RELATED KINASE 1 (SnRK1) to affect anthocyanin accumulation [56,57].…”
Section: Plos Onementioning
confidence: 99%
“…For example, JA enhances the accumulation of anthocyanin [61], and JAZ proteins interact with transcription factors or energy sensor SNF1-RELATED KINASE 1 (SnRK1) to affect anthocyanin accumulation [56,57]. In Salvia miltiorrhiza hairy roots, JA-induced tanshinone biosynthesis is mediated by JAZ proteins and SmJAZ8 acts as a core repressor [59,60]. Also, it has been reported that the enhanced accumulation of Amaryllidaceae alkaloids can be elicited by addition of exogenous JAs treatment in Amaryllidaceae plants [37,38,62,63], but the exact molecular regulation mechanisms, including those related with JAZs, are still obscure in this plant family.…”
Section: Plos Onementioning
confidence: 99%
“…Total phenolics and total flavonoids were detected as previously described with some modifications [5,32]. The absorbance of the samples for the total phenolics and total flavonoids analyses was measured at 765 nm and 506 nm, respectively.…”
Section: Determination Of Total Phenols and Total Flavonoidsmentioning
confidence: 99%
“…More than 40 tanshinones and 20 hydrophilic phenolic acids have been isolated and identified from S. miltiorrhiza [3]. Tanshinones including dihydrotanshinone I (DT-I), cryptotanshinone (CT), tanshinone I (T-I) and tanshinone IIA (T-IIA) in S. miltiorrhiza are biosynthesized through the mevalonic acid (MVA) and 2-C-methyl-D-erythritol-4-phosphate (MEP) pathways [4,5]. Phenolic acids including salvianolic acid B (Sal B) and rosmarinic acid (RA) in S. miltiorrhiza are biosynthesized via the phenylpropanoid and the tyrosine-derived pathways [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Male sterility plays an extremely important role in heterosis utilization and hybrid seed yield of crops and its use has successfully increased crop yield [11][12][13]. S. miltiorrhiza is generally used as a medicinal plant and has been widely used to treat cardiovascular and cerebrovascular diseases, hyperlipidemia, and acute ischemic stroke [14][15][16][17][18]. There are many traditional Chinese medicines such as Fufang Danshen Tablets and Danshen injections, etc., which contain active ingredients extracted from S. miltiorrhiza [19].…”
Section: Introductionmentioning
confidence: 99%